(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to analyze the effect of auditee characteristics, audit fee, and public accounting firm size to determine the issuance of qualified audit opinion on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2012-2016 period. The independent variables in this research are current Ratio, receivable to sales ratio, net profit margin ratio, operating margin to total assets ratio, debt ratio, audit fee, and public accounting firm size. SPSS Statistics version 22 is used to test the hypothesis. The result shows that the debt ratio influences to determine the qualified audit opinion. Meanwhile, the current Ratio, receivable to sales ratio, net profit margin ratio, operating margin to total assets ratio, audit fee, and public accounting firm size does not affect the qualified audit opinion.